The multidisciplinary approach to biochemistry laboratory education - HAKLAR, GONCAGÜL; YÜKSEL, MERAL (TURKISH BIOCHEM SOC, 2013)
European Union's Life Long Learning Programmes and the Bologna Process describe new classifications. Related with these new classifications, our higher education system is being restructured under the name of National Qualification Frameworks. Between the National and European programmes comparability and the transparency is expected to promote life-long learning. The workshop named as Biochemistry Laboratory Training Workshop on Multi-Disciplinary Approach was held on 3-4 May 2012 in Ankara with the scope of biochemistry laboratory culture, education, laboratory work and experimental methodology consisted of gain and the development of scientific thinking skills. As a result of the workshop, it was mentioned that, biochemistry theoretical course and biochemistry laboratory are being taught in different faculties, colleges and vocational schools. Biochemistry's interdisciplinary character, its' being closely related to physiology, being based on chemistry/physics principles and conceptions and extending increasingly to molecular biology, molecular genetics and nanoscience have brought new approaches in Biochemistry and Biochemistry Laboratory Education. The need for developing new applications using alternative materials leads to modern experimentation to be employed in teaching biochemistry laboratory at different educational establishments. Taking into account the previous studies, the core laboratory training, achievements and targets identified. The timetable of the teaching-learning and the evaluation process were discussed. Besides the core laboratory programme, the awareness of scientific research projects was discussed. It was also noted the coordination between the different programmes and the basic mandatory structure of the laboratories during the time of adaptation to the European. In addition, difficulties in provision of equipment and supplies, the responsibility of governments, readiness and competencies of students, teaching staff qualifications were discussed for the effective laboratory training. Young scientists and graduate students had actively participated in the workshop. Finally positive steps have been taken to develop the ability to work with the cultures of scientific thinking.
Keywords: biochemistry laboratory; laboratory training; National Qualifications Framework; WORKSHOP HELD; BIOLOGY